Differential CD4 T Regulatory Cell Phenotype Induced by Andes Hantavirus Glycoprotein - Saavedra, Farides; Garrido, Jose L.; Fuentes-Villalobos, Francisco; Calvo, Mario; Riquelme, Raúl; Rioseco, María Luisa; Chahín, Carolina; Ferreira, Leonila; Alvarez, Raymond; Nova-Lamperti, Estefania; Barria, Maria Ines (Frontiers in Cellular and Infection Microbiology, 2020)
Hantavirus cardiopulmonary syndrome (HCPS) caused by Andes orthohantavirus (ANDV) in South America is a public health threat due to the significant rate of mortality and the lack of a specific treatment. Interestingly, the virus does not produce cytopathic effect, thereby the strong antiviral immune response is suspected to contribute to pathogenesis, hence is important to understand the balance between protective and harmfully immunity. CD4+ T regulatory cells (Treg) are essential to control an exacerbated immune response. In human ANDV infection, little is known about CD4+ Treg cells, which may be involved in control immunopathology associated to the infection. In this report, we characterize the phenotype of memory CD4+ Tregs in a HCPS survivor’s cohort. Based on the expression of CXCR3, CCR4 and CCR6, we identified different Th-like Treg populations in ANDV survival’s PBMCs. In addition, the effect of ANDV-glycoprotein virus like particles (VLP) was determined. We demonstrated that memory CD4+ Treg from HCPS present a specific phenotype, showing higher frequency of PD-1 compared to healthy donors (HD). In addition, it was observed a decrease in the frequency of Th1-like memory CD4+ Treg in HCPS, important to highlight that this signature could be preserved even years after resolution of infection. Moreover, to gain insight in the mechanism involved, we evaluated whether ANDV-glycoprotein (GP) VLP could modulate CD4+ Treg. Interestingly, ANDV-GP VLP induced a decrease in the frequency of CXCR3 (Th1-like) and an increase in CCR4 (Th2-like) memory CD4+ Treg in both HD and HCPS PBMCs, indicating that ANDV-GP could specifically act over CXCR3 and CCR4 in CD4+ Treg. This report contributes to the study of human CD4+ Treg cells in ANDV infection.